Styling the Surveillance Self in Fashion Media: Strategies of Sexualization and Sentimentality - Rogers, Louisa (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
The burgeoning market for wearable technologies with surveillance capabilities is reorienting our relationship with our bodies, privacy, and digital data. This expanding sector has prompted an exploration into how the surveillance of the individual body has been normalized more broadly in the fashion sphere through its visual communications practice. To this end, a multimodal critical discourse analysis following an adapted framework examined a series of photographic editorials and identified two overarching trends that characterize the representation of surveillance in female-focused fashion consumption contexts. Firstly, by adopting a visual style that uses analog aesthetics and obsolescent technology, contemporary surveillance’s obtrusive and expansive reality is obscured and replaced with hauntological nostalgia. Secondly, by framing the act of self-surveillance via screen technologies as erotically charged and potentially empowering, the body’s surveillance is celebrated rather than scrutinized. With close reference to two specific case studies, I demonstrate how these visual treatments can be interpreted as downplaying concerns about privacy and assisting in accelerating the collapse between public and private spheres. I argue that the fashion media’s aesthetic softening of surveillance has culturally foreshadowed an expansion of surveillance capitalism manifesting in the current interest in, and demand for, fashionable wearables.